2015
DOI: 10.1021/jz502588x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Excess Electrons in Nonlinear Optical Response

Abstract: The excess electron is a kind of special anion with dispersivity, loosely bounding and with other fascinating features, which plays a pivotal role (promote to about 10(6) times in (H2O)3{e}) in the large first hyperpolarizabilities (β0) of dipole-bound electron clusters. This discovery opens a new perspective on the design of novel nonlinear optical (NLO) molecular materials for electro-optic device application. Significantly, doping alkali metal atoms in suitable complexants was proposed as an effective appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 195 publications
(119 citation statements)
references
References 94 publications
2
117
0
Order By: Relevance
“…Thermal poling was originally studied as a process to induce nonlinear optical properties and electro‐optic effects in isotropic glass materials; it was recently reported that thermal poling can also be used as an efficient way to increase the indentation fracture toughness of SLS glass . Thermal poling is typically done by applying a high electric field (on the order of MV/m) across the glass at an elevated temperature, which facilitates diffusion of Na + ions from the surface in contact with the anode to the surface in contact with the cathode, and then cooling the sample while holding the electric field to freeze any nonequilibrium distribution or polarization of ions in the glass matrix .…”
Section: Introductionmentioning
confidence: 99%
“…Thermal poling was originally studied as a process to induce nonlinear optical properties and electro‐optic effects in isotropic glass materials; it was recently reported that thermal poling can also be used as an efficient way to increase the indentation fracture toughness of SLS glass . Thermal poling is typically done by applying a high electric field (on the order of MV/m) across the glass at an elevated temperature, which facilitates diffusion of Na + ions from the surface in contact with the anode to the surface in contact with the cathode, and then cooling the sample while holding the electric field to freeze any nonequilibrium distribution or polarization of ions in the glass matrix .…”
Section: Introductionmentioning
confidence: 99%
“…[8,55] First, as eries of supersalts (BLi 6 ) + (X) À (X = F, LiF 2 ,B eF 3 ,B F 4 ), [8a] (M) + (BF 4 ) À (M = FLi 2 ,O Li 3 ,N Li 4 ), [8b] (M 3 O) + (Al 13 ) À (M = Na, K), [8c] (Na 2 X) + (Y) À (X = SCN, OCN, CN;Y= MgCl 3 ,Cl, NO 2 ) [30a] were theoretically constructed and predicted to be new inorganic NLO molecules in view of their considerable NLO responses. Moreover,w ith their superiora bility to offer valence electrons, superalkalis can serve as excellent sourceso fe xcess electrons [57] to design unique compounds,s uch as electrides [58] and alkalides, [59] whiche xhibit extraordinarily large NLO responses. Wang et al [8d] presented the first evidencef or superalkalibased electrides (M 3 O) + (e@C 20 F 20 ) À (M = Na, K), where the excess electron is protected in the C 20 F 20 cage with as ufficient interior electron attractive potential (see Figure9a).…”
Section: Applications Of Superalkalismentioning
confidence: 99%
“…It is noteworthy that selecting a proper method to calculate the hyperpolarizability of a system is a challenging task. The quadratic configuration interaction including single and double substitutions (QCISD) and the second-order Møller-Plesset perturbation (MP2) methods are suitable to for calculating hyperpolarizability, but they are very costly for relatively larger systems [17,42]. On the other hand, the B3LYP method has overestimated the hyperpolarizabilities for some large systems [43].…”
Section: Computational Detailsmentioning
confidence: 99%